The sintering-temperature-related microstructure and phase assemblage of alumina-doped and alumina–silica-co-doped 3-mol%-yttria-stabilized tetragonal zirconia. (August 2015) - Samodurova, Anastasia; Vengust, Damjan; Kocjan, Andraž; Kosmač, Tomaž
Graphical abstract: Abstract : The influence of higher sintering temperatures on the microstructure and equilibration of alumina-doped and alumina–silica-co-doped 3-mol%-yttria-stabilized tetragonal zirconia ceramics was investigated. The temperature-related (⩾1550 °C) penetration of the silica phase from the grain junctions into the grain boundaries was accompanied by the emergence of a fraction of larger, heterogeneous grains. The overall partitioning process was slower in the co-doped material, increasing the resistance to ageing, while upon cooling the partitioned yttria-rich phase was found to be tetragonal ( t′ -ZrO2 ).